(untitled) (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2023)
Filariasis is chronic and if not treated properly can lead to permanent disability. In this case, the main vectors of Wuchereria bacrofti are Culex, Anopheles and Aedes mosquitoes. Symptoms that can arise from filariasis are more pronounced in men, due to heavier physical labor. In Southeast Asia, Indonesia is one of the 11 countries endemic for filariasis. Filariasis in Indonesia was first reported by Haga and Van Eecke in 1889 in Jakarta with the discovery of scrotal filariasis. Reported clinical cases tend to increase from year to year due to the large number of cases found along with districts / cities that carry out target data collection before the provision of mass preventive drugs (POPM) filariasis from 2014-2022 cumulative cases of chronic filariasis with the highest disability in East Nusa Tenggara. Indonsia can break the chain of filariasis spread by Breaking the chain of filariasis by mass drug administration in endemic areas once a year for 5 consecutive years and Preventing and limiting disability by self-management of filariasis cases. The parasite is spread using mosquito vectors as intermediate hosts and humans or monkeys and dogs as final hosts. When the mosquito sucks the blood of a human/animal where the sheath detaches and then penetrates the abdominal wall Mosquitoes carrying microfilariae migrate into the mosquito’s abdomen and in the muscle or fatty tissue in the chest area. Filariasis prevention is done by avoiding infective mosquito bites and eradicating risks associated with Filariasis incidence such as those from the environment and changes in community behavior as well as maintaining and developing local wisdom. Identifying vectors by detecting the presence of infective larvae in mosquitoes using human bait. For treatment, the drug used is DEC (diethylcarbamazine citrate) is the main drug in both treatments crowds or individuals. DEC kills microfilariae and for adult worms.